A State of the Art of Communicative Competence Theory - Fauziati, Endang (Ahmad Dahlan Journal of English Studies, 2015)
What is actually involved in learning a foreign language? What kinds of knowledge and skill to be mastered? The answer to these questions deals with language competence, that is, the knowledge of the language and the ability to use that knowledge to interpret and produce meaningful texts appropriate to the situation in which they are used. It corresponds with Ellisâs (1996: 74) statement that the goal of learning a foreign language âis concerned with the ability to use language in communicative situationsâ and the point of language teaching is to help the students communicate or to develop what Hymes (1972) referred to as âcommunicative competenceâ.The idea of communicative competence in language teaching is not really new. It got its first popularity in the 1960s and 1970s when communicative approach was initially adopted. This approach could be said to be the product of educators and linguists who were dissatisfied with the audiolingual and grammar-translation methods of foreign language instruction. They believed that students were not learning enough realistic, whole language; they were at a loss to communicate in the culture of the target language.Â Â Â Â Â Â Â Â Â Â Â  This paper tries to provide a review on the kind of knowledge and skill needed to be mastered in foreign language learning, that is, the communicative competence. Linguists often emphasize different components in their description of communicative competence. This discussion will cover the categorization of the knowledge and skill involved in language use offered by different scholars such as Dell Hymes (1972), Canale and Swain (1980), Bachman (1980), Bachman and Palmer (1986) Celce-murcia et al. (1995), and Pawlikowska-Smith (2002).